Conflict Management in Islamic Boarding Schools: A Framework Based on Local Wisdom for Educational Institutions - Rakhman, Fathor; Fauzan, Mohammad (JURNAL AL-TANZIM, 2025)
This research focuses on understanding how conflicts that occur in Islamic boarding schools are managed and the strategies used to resolve these conflicts. This research uses a qualitative method with a case study. Data was collected through in-depth interviews, observations, and documentation. The collected data was analyzed using data analysis techniques according to Miles and Huberman, which included data reduction, data presentation, and a conclusion. The study results show that conflicts in Pesantren appear in various forms, such as political, economic, task, and organizational conflicts. The conflict management strategies implemented include Tabayyun (clarification), deliberation, and the application of the Amar Ma’ruf Nahi Munkar value (inviting goodness and preventing evil). This study found that effective conflict management can increase cooperation, motivation, and discipline among Pesantren members. Conversely, poorly managed conflicts can degrade the performance of institutions and create internal tensions. The implication of this study is the importance of implementing conflict management strategies based on religious values to create a harmonious environment and support the development of Islamic boarding schools.